Limitations of the lump-sum package contract policy in implementation of scientific and technological tasks funded by State budget - Hien, Pham Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The funding modality of package contract to perform scientific and technological (S&T) tasks has currently not supported for effective management of financial resources for implementation of research projects, not created an enabling environment for scientists, thus it does not really promote scientific research. This article focuses on limitations of the package contract policy and its impact on the implementation of S&T tasks funded by State budget, and suggests direction for improving the policy. Code: 13082601